Synergizing Entrepreneurial Ecosystem, Entrepreneurial Leadership, and Dynamic Capability for Creative SME Performance in East Java - Arif, Moh. Erfan (Journal of Development Economic and Social Studies, 2025)
An enabling entrepreneurial ecosystem constitutes a critical foundation for enhancing business performance, stimulating innovation, generating employment, and advancing economic development. Nevertheless, the realization of such optimal conditions remains uneven across regions and nations, especially within the context of developing economies. This study examines the nexus between the performance of creative Small and Medium-sized Enterprises (SMEs) and several pivotal determinants, namely the entrepreneurial ecosystem (EE), entrepreneurial leadership (EL), and dynamic capabilities (DC). Employing a quantitative research approach, the study surveyed 193 creative industry SME actors in East Java Province, Indonesia. A non-probability purposive sampling technique was utilized, and data were analyzed using structural equation modeling (SEM) with SmartPLS 4. The findings reveal that EE, EL, and DC significantly contribute to enhancing SME performance in the creative industry. Notably, the results exhibit a unique pattern, aligning more closely with findings from developed countries, despite the research being conducted in a developing economy. This suggests that EE can be effectively developed through the active engagement of relevant stakeholders and the prevailing cultural context of a region or nation, even within the constraints of a developing country setting.